ANALYSIS OF SCIENCE PROCESS SKILL COMPONENTS IN NATURAL AND SOCIAL SCIENCE BOOKS FOR CLASS V SEUNEUBOK JOHAN EAST ACEH PRIMARY SCHOOL - Nurmayani Daulai; Siti Mayang Sari; Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to analyze the components of science process skills innatural and social science books for class V at the Seuneubok Johan stateelementary school. The scientific approach (observing, asking, analyzing,concluding, communicating and creating) is part of the Science Process Skills.This research is researchdescriptive or descriptive research is research that aimsto describe a phenomenon or situation without manipulationobject study. Thestages in this research are selecting textbooks, taking and determining samples,analyzing the components of Science Process Skills in the books, and drawingconclusions. The results of this research are the skills componentsprocess In thenatural and social science books for class V of the Seuneubok Johan stateelementary school, East Aceh, there are still few components of science processskills, namely observing, communicating and asking questions. There are noanalyzing, concluding and creating components yet, so follow-up is needed insubsequent research, so that the science process skills components in naturaland social science books are optimal.